Long-Read Sequencing Identifies Novel Pathogenic Intronic Variants in Gitelman Syndrome. Issue 2 (9th February 2023) - Viering, Daan H.H.M.; Hureaux, Marguerite; Neveling, Kornelia; Latta, Femke; Kwint, Michael; Blanchard, Anne; Konrad, Martin; Bindels, René J.M.; Schlingmann, Karl-Peter; Vargas-Poussou, Rosa; de Baaij, Jeroen H.F.
Abstract : Abstract : Significance Statement: Gitelman syndrome is caused by biallelic pathogenic variants in SLC12A3, which encodes the thiazide-sensitive sodium-chloride cotransporter (NCC). A subset of patients with Gitelman syndrome has only one specific pathogenic variant identified. In this study, long-read sequencing identified 46 previously undetected variants in 95 patients with suspected Gitelman syndrome. A midigene splice assay confirmed the pathogenicity of intronic variants. The data show that both intronic and exonic variants were missed previously and that former detection of one SLC12A3 variant predicts identification of an additional variant. The findings advocate long-read sequencing, complemented with a midigene splice assay, for intronic variants, as a second-tier diagnostic test in patients with one pathogenic SLC12A3 variant. Background: Gitelman syndrome is a salt-losing tubulopathy characterized by hypokalemic alkalosis and hypomagnesemia. It is caused by homozygous recessive or compound heterozygous pathogenic variants in SLC12A3, which encodes the Na + -Cl − cotransporter (NCC). In up to 10% of patients with Gitelman syndrome, current genetic techniques detect only one specific pathogenic variant. This study aimed to identify a second pathogenic variant in introns, splice sites, or promoters to increase the diagnostic yield. Methods: Long-read sequencing of SLC12A3 was performed in 67 DNA samples from individuals with suspected Gitelman syndrome in whom a single likely pathogenic or pathogenic variant was previously detected. In addition, we sequenced DNA samples from 28 individuals with one variant of uncertain significance or no candidate variant. Midigene splice assays assessed the pathogenicity of novel intronic variants. Results: A second likely pathogenic/pathogenic variant was identified in 45 (67%) patients. Those with two likely pathogenic/pathogenic variants had a more severe electrolyte phenotype than other patients. Of the 45 patients, 16 had intronic variants outside of canonic splice sites (nine variants, mostly deep intronic, six novel), whereas 29 patients had an exonic variant or canonic splice site variant. Midigene splice assays of the previously known c.1670-191C>T variant and intronic candidate variants demonstrated aberrant splicing patterns. Conclusion: Intronic pathogenic variants explain an important part of the missing heritability in Gitelman syndrome. Long-read sequencing should be considered in diagnostic workflows for Gitelman syndrome.